Effectiveness of Reality Group Counseling in Enhancing Ego Identity Among Indonesian High School Students: A Pretest-Posttest Experimental Study - Bakhrudin All Habsy; Ezza Wahyu Dian Cantika; Colin Stanley; Ela Nur Fadilah; Issac Briyan Alisyahbana; Ach. Sudrajad Nurismawan (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
An individual's ego identity, a self-image that grows, develops, and internalizes through social interaction, is the culmination of the psychosocial phases they have experienced. This study examined the effectiveness of reality group counseling in enhancing the ego identity of high school students, using a pretest-posttest control group experimental design. Based on the ego identity inventory results, eight students were identified as having low ego identity. The study used two types of instruments: treatment and measurement. The treatment instrument was a reality group counseling implementation guide, and the measurement instrument was an ego identity inventory with a total item validity above the critical r value of 0.344 and a reliability coefficient of 0.957, indicating that the inventory is reliable and suitable for research purposes. Researchers analyzed the data using non-parametric statistical tests. The hypothesis testing yielded an N-Gain percentage of 109.18 > 76 and an Asymp. Sig. (2-tailed) value of 0.012 < 0.05. Therefore, the study rejected the null hypothesis and accepted the alternative hypothesis, suggesting that reality group counseling effectively enhances the ego identity of high school students. Keywords: ego identity, reality group counseling, high school students